Public Libraries Institution of Mass Education - Patel, Rakesh Kumar (JOURNAL OF INDIAN EDUCATION, 2017)
The paper explicates the process of establishing public libraries in the remote villages of Uttar Pradesh as an attempt to strengthen the fundamental democratic institutions of rural India. Village library is relatively a newer public sphere where villagers could sit together, read, learn and discuss on various issues in a democratic environment. It is our empirical perception that standard books and literature are not available in remote villages. There is a huge gap between rural and urban educational infrastructure. Opening village library was an effort to bridge the aforesaid gap. It has been argued that opening village library would strengthen democratic processes and ensure empowerment of marginalised and deprived village dwellers. After seven decades of our Independence, it is a grim situation that villagers are not even familiar with the concept of library. This work of opening village libraries was initiated by a team of administrative officers who strongly believe in the concept of paying back to the society.